Does CEO emotional bias affect performance? - Yasmine Souissi; Anis Jarboui (Cogent Economics & Finance, 2018)
This article is focused on tackling the issue of the impact of the bank CEO's emotional bias on the Tunisian banks' performance level while accounting for the mediating role of the control systems. In this regard, an empirical study has been set up through a questionnaire undertaken as an appropriately fit data collection method administered to a sample of 100 CEOs of Tunisian banks. Actually, the present research is intended to help in reflecting an original approach, since it serves to highlight the behavioral aspects' crucial role in explaining the performance level within the framework of the organizational architecture theory. To the best of our knowledge, this work represents a pioneering study that deals with exploring such a research area within the Tunisian context. Indeed, the achieved results reveal with no doubt that the behavioral dimension constitutes a central aspect in the organizational architecture as it helps greatly in reflecting the intermingling of the incentive aspect with the evaluation system with respect to the accounts manager.
Keywords: 330; behavioral management; emotional biases; organizational architecture theory; control systems